Latest cosmological constraints on Cardassian expansion models including the updated gamma-ray bursts - Liang, Nan; Wu, Pu-Xun; Zhu, Zong-Hong (Research in astronomy and astrophysics, 2011)
Abstract We constrain the Cardassian expansion models from the latest observa- tions, including the updated Gamma-ray bursts （GRBs）, which are calibrated using a cosmology independent method from the Union2 compilation of type Ia supernovae （SNe Ia）. By combining the GRB data with the joint observations from the Union2 SNe Ia set, along with the results from the Cosmic Microwave Background radia- tion observation from the seven-year Wilkinson Microwave Anisotropy Probe and the baryonic acoustic oscillation observation galaxy sample from the spectroscopic Sloan Digital Sky Survey Data Release. we find significant constraints on the model oarameters of the original Cardassian model ΩM0=0.282-0.014^0.015,n=0.03-0.05^＋0.05 and n=-0.16-3.26^＋0.25,β=0.76-0.58^＋0.34 of the modified polytropic Cardassian model, which are consistent with the ACDM model in a l-or confidence region. From the reconstruction of the deceleration parameter q（z） in Cardassian models, we obtain the transition redshift ZT = 0.73 ± 0.04 for the original Cardassian model and ZT = 0.68 ± 0.04 for the modified polytropic Cardassian model.